2016
DOI: 10.1080/00207233.2016.1185327
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of the pernicious and toxic weed parthenium into an organic fertilizer by vermicomposting

Abstract: In what is believed to be the first study of its kind, the compositions of the toxic and allelopathic weed parthenium, and its vermicompost, have been investigated using UV-visible and Fourier transform infrared spectroscopy, thermogravimetric analysis, differential scanning calorimetry, gas chromatography-mass spectroscopy, and scanning electron microscopy. The studies reveal that the weed is transformed into a totally benign organic fertilizer during the course of its vermicomposting. This is indicated by su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Such compounds include relatively simple aliphatics, e.g., methanol, ethanol, acetone and ethyl ether; aromatics, e.g., phenol and hydroxyquinoline; and complex growth regulators, e.g., gibberellins and cytokines [44]. As VC is rich in organic chemicals [45][46][47][48], it is likely to contain one or more of these compounds which enhance germination success. It has already been shown that plant growth hormones that are present in VC facilitate seed germination [49,50].…”
Section: Effect Of Vermicompost On Seed Germinationmentioning
confidence: 99%
“…Such compounds include relatively simple aliphatics, e.g., methanol, ethanol, acetone and ethyl ether; aromatics, e.g., phenol and hydroxyquinoline; and complex growth regulators, e.g., gibberellins and cytokines [44]. As VC is rich in organic chemicals [45][46][47][48], it is likely to contain one or more of these compounds which enhance germination success. It has already been shown that plant growth hormones that are present in VC facilitate seed germination [49,50].…”
Section: Effect Of Vermicompost On Seed Germinationmentioning
confidence: 99%
“…The decreases in humification index ratios (Q 2/6 , Q 2/4 ) indicates decomposition and degradation of organic compounds by earthworms. Hussain et al (2016b) studied UV-vis spectroscopy analysis to assess the degree of humification during vermicomposting of toxic parthenium weed. The results reveal that the humification index (Q 4/6 ) values of initial parthenium weed (7.29) were reduced (1.89) after vermicomposting.…”
Section: Ultraviolet-visible (Uv-vis) Spectroscopy Analysis In Vermicmentioning
confidence: 99%
“…; Khan & Abbasi ; Abbasi & Abbasi a,b; Hussain et al . ; Premalatha et al ., 2014). In this manner the entire E. prostrata biomass used in SHEFROL ® has the potential to be assimilated in nature, leaving nothing to waste.…”
Section: Discussionmentioning
confidence: 99%
“…Potential of the utilization of E. prostrata removed/harvested from SHEFROL V R As has been shown by us earlier, when weedy species like E. prostrata die in the channels and are removed, or are harvested to check overgrowth, they can be utilized via anaerobic digestion to obtain energy in the form of flammable CH 4 -CO 2 mixture called biogas (Abbasi et al 2009;Tauseef et al, 2013). Spent E. prostrata can be converted to organic fertilizer through vermicomposting (Gajalakshmi et al 2002;Khan & Abbasi 1998;Abbasi & Abbasi 2011a,b;Hussain et al 2015Hussain et al , 2016Premalatha et al, 2014). In this manner the entire E. prostrata biomass used in SHEFROL V R has the potential to be assimilated in nature, leaving nothing to waste.…”
Section: The Present Findings In the Context Of The Performance Of Comentioning
confidence: 99%